Pengaruh Media Sosial terhadap Regulasi Emosi pada Remaja - Khasanah, Faidatul (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the influence of social media use on emotion regulation among adolescents. Social media has become an integral part of daily life, yet its use brings various psychological consequences. Literature review shows that social media can serve as a positive tool for emotional expression and social support, but excessive use may trigger anxiety, stress, and difficulties in emotion regulation. Adolescents with strong digital literacy are more likely to mitigate the negative impact of social media on their mental health. This study emphasizes the importance of digital literacy education as well as parental and school involvement in guiding adolescents to use social media healthily. Positive interactions that occur online can strengthen emotional regulation skills because teenagers feel supported, accepted, and have a safe space to share emotional experiences.